How does a lifetime of painful experiences influence sensations and beliefs about pain in adults with severe haemophilia? A qualitative study. Issue 26 (18th December 2022) - McLaughlin, P.; Hurley, M.; Chowdary, P.; Stephensen, D.; Khair, K.
Abstract: Purpose: To explore the life experiences of pain in people with severe haemophilia and understand how such experiences influence beliefs and sensation of pain in adulthood. Methods: A qualitative inquiry approach using focus groups and semi-structured individual interviews was used. Participants included people with severe haemophilia living with chronic pain. Data were analysed using reflexive thematic analysis. Results: Fourteen men with a median age of 47 (range 23–73) agreed to take part. Eleven participated in two focus groups and three were interviewed over telephone. Two themes were conceptualised from the data: (i) haemophilia and pain – an evolving life biography (the personal narrative, historical, social, and medical context, continuous adaptation of activity choices, surveillance of pain and its meaning); (ii) " My normal isn't normal " – identity and self-agency (pain as a feature of life and identify with severe haemophilia, loss of enjoyable activities balanced against staying active, barriers to participation). Conclusions: Pain is a constantly evolving, lifetime feature for many adults with haemophilia and it is viewed as part of their identity with their condition. Healthcare professionals working in haemophilia should try to better understand the influence of an individuals lived experience with their haemophilia on beliefs and behaviours of pain. Implications for rehabilitation: Severe haemophilia is a rare bleeding disorder that results in musculoskeletal joint disease. Adults with severe haemophilia have experienced multiple episodes of bleeding related musculoskeletal pain since childhood. Pain beliefs and behaviours in adulthood appear to be influenced by a lifetime of painful experiences associated with haemophilia. In order to better support people with haemophilia and chronic pain, healthcare professionals in haemophilia need to better understand how an individuals lived experience of pain helps inform their beliefs about it.